PROSES EKSTERNALISASI DALAM KONSTRUKSI SOSIAL TERHADAP REALITAS PENYAKIT KUSTA DI DESA JENGGAWAH KECAMATAN JENGGAWAH KABUPATEN JEMBER - Luthviatin, Novia (FKM - UNEJ, 2011)
The purpose of this study was to know the process of externalization in social construction of leprosy reality in Jenggawah Village. This research is a qualitative research with a phenomenological approach. The primary data obtained through in-depth interviews to the informant. At first, public mention of leprosy as a disease and symptoms are neck, is considered a curse, witchcraft, and because kesambet, rheumatism, diabetes. Although then there is a new generation with changes in views or knowledge about leprosy, its symptoms, and treatment procedures that emerged in Dusun Babatan. Attitudes formed on the patients family is likely to receive what the state of the patient. Some patients family provides further support to patients can recover but some will not care because they do not know for sure about the disease sufferers. While public attitudes about tend not to accept the condition of the patient. Action taken by the society is to make evasion in various forms by reason of contempt against the smell and the shape of the wound and the fear of contracting the illness. While action of sufferers is hiding from the public. Keywords: externalization in social construction, leprosy reality, phenomenology